In vitro capacitation and acrosome reaction of goat sperms in Tyrode's modified solution* - CHEEMA, S; SANGHA, G K; GURAYA, S S (The Indian Journal of Animal Sciences, 2014)
Percent motility, hyperactive motility (capacitation) and acrosome reaction in goat epididymal spermatozoa duringincubation in vitro at 38.5°C in m-TALP (Tyrode's modified solution containing albumin, lactate and pyruvate) mediumsupplemented with taurine and epinephrine as motility factors plus BSA under liquid paraffin. in a CO2 incubator, were studied. The percent capacitation and acrosome reaction can be estimated by the onset of hyperactive motility andshedding of acrosome reaction under an inverted microscope. The percentage of hyperactive motile spermatozoa is maximum. (72.40 ± 1.43) at 4hr of incubation, The per cent acrosome reaction increased progressively with maximum of 60.20  ± 0.79 at fifth hr of incubation. The results suggested that the goat epididymal spermatozoa can be Induced to undergo capacitation and acrosome reaction in vitro in a chemically defined medium.